Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Keaktifan Belajar Siswa pada Pembelajaran Tematik Kelas V Tema 8 di SD Negeri 1 Selo Kabupaten Grobogan Jawa Tengah - Muhamad Rizqi Amridzal Luthfi; Choirul Huda; Joko Susanto (Jurnal Paedagogy, 2021)
This study aims to apply the Discovery Learning learning model to increase student learning activity in the thematic learning of class V SD Negeri 1 Selo. This research method used classroom action research which is carried out in 3 cycles. The subjects of this study were fifth grade students of SD Negeri 1 Selo, totaling 14 students. The instrument used observation and tests. While the data analysis technique used descriptive quantitative analysis. The results of this study indicate that student learning activity has increased. Learning activity in cycle 1, meeting 1, was 59.77%, followed by meeting 2, which was 60%. Based on the results of cycle 1, it has shown an increase. The increase that occurred in cycle 1 also occurred in cycle 2. In cycle 2, meeting 1, the percentage of active learning was 68.09%. Furthermore, at the second meeting, it was 69.53%. Based on the results of cycle 2, it has also shown an increase. Then it increased in cycle 3 of meeting 1 to 75.48%, and meeting 2 of 79.53%.